Science and Pension Politics - Florian Blank (Wirtschaftsdienst)
Abstract Recently, a German federal government commission presented its findings on how to reform the pension system. Part of the commission’s report and the subsequent debate deal with the role of experts and scientific advisors in pension politics. This article contributes to the debate and seeks to refute claims that experts should have more competences.